2005
DOI: 10.1111/j.1469-0691.2004.01029.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between tumour necrosis factor gene polymorphisms and the clinical types of patients with chronic hepatitis B virus infection

Abstract: A PCR restriction fragment length polymorphism assay was used to analyse single-nucleotide polymorphisms in the tumour necrosis factor (TNF)-alpha and TNF-beta genes of 56 patients with chronic severe hepatitis B virus (HBV) infection, 71 patients who either had chronic mild HBV infection or who were asymptomatic carriers, and 90 healthy controls. The serum TNF-alpha concentrations in patients with chronic severe HBV infection were compared to those of 30 healthy controls by radioimmunoassay. The frequencies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 15 publications
1
31
0
Order By: Relevance
“…Nonetheless, he found that the haplotype -308 G/ -238 G was associated with HBV persistence. On the other hand, Xu et al (2005) verified a higher frequency of both, TNF -308 GA and the allele A in chronic patients with severe disease in relation to controls, asymptomatic patients and patients with mild disease. Nevertheless, they did not see any difference between chronic patients, as a single group, and controls.…”
Section: Discussionmentioning
confidence: 80%
“…Nonetheless, he found that the haplotype -308 G/ -238 G was associated with HBV persistence. On the other hand, Xu et al (2005) verified a higher frequency of both, TNF -308 GA and the allele A in chronic patients with severe disease in relation to controls, asymptomatic patients and patients with mild disease. Nevertheless, they did not see any difference between chronic patients, as a single group, and controls.…”
Section: Discussionmentioning
confidence: 80%
“…In specific, the importance of cytokines such as TNF-a, which acts as a potent pro-inflammatory cytokine for the clearance of viral infection, has been highlighted for many years [18], and numerous studies have been conducted to identify polymorphisms of TNF-a promoters that affect susceptibility to persistent HBV infection [16,19,20]. Of the various polymorphisms, those at positions -308 and -238 are the most well-studied targets [10][11][12][13][14][15]. Until today, however, no analysis has been performed on the relationship between polymorphisms of TNF-a promoters and outcomes of HBV treatment with antiviral agents.…”
Section: Discussionmentioning
confidence: 99%
“…Among the various single nucleotide polymorphisms (SNPs) in the TNF-a promoter region, -238 G to A and -308 G to A polymorphisms were vigorously investigated [10][11][12][13][14][15]. Although the results were not consistent, it was notable that TNF-a promoter -238 G to A polymorphism was associated with chronic hepatitis B and progression of HBV infection [10,13,15], and that -308 G to A polymorphism was associated with HBV clearance and antibody production [11].…”
Section: Introductionmentioning
confidence: 99%
“…The diagnoses were complied with the diagnostic criteria of the 2000 Xi'an Viral Hepatitis Management Scheme issued by the Chinese Society of Infectious Diseases and Parasitology, and the Chinese Society of Hepatology, of the Chinese Medical Association (36). The standards for diagnoses of AHB, CHB, and CSHB have been described in detail previously (37,38). Briefly, AHB patients are defined as those who displayed hepatitis B surface Ag (HBsAg)-negative conversion within 6 mo after the initial onset of symptoms due to HBV infection.…”
Section: Subjectsmentioning
confidence: 99%